2005
DOI: 10.1002/eji.200425775
|View full text |Cite
|
Sign up to set email alerts
|

Dual regulation of BCR‐mediated growth inhibition signaling by CD72

Abstract: CD72 has been reported to regulate BCR‐mediated signals both positively and negatively. SHP‐1 and Grb2 bind, respectively, to ITIM1 and ITIM2 of CD72. We generated transformed B cell lines with an immature phenotype following J2 virus infection of splenocytes from CD72–/– and wild‐type (Wt) mice. The transformed lines were infected with retroviral vectors carrying Tyr (Y) to Phe (F) substitutions in the ITIM sequences (ITIM1 mutated: Y7/F; ITIM2 mutated: Y39/F; and both ITIM mutated: Y7,39/F). Cross‐linking of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
15
0

Year Published

2006
2006
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 34 publications
1
15
0
Order By: Relevance
“…36,37 CD72 is a 45-kDa immunoreceptor tyrosine-based inhibitory motif (ITIM) domaincontaining type II transmembrane protein that has been shown to affect intracellular signaling in B cells through its ability to associate with the tyrosine phosphatase SHP-1 and the adaptor protein Grb2. 38,39 Plexin-B1 has a type-I PDZ ligand domain at its C terminus, enabling it to interact with cytosolic proteins that have 1 or more PDZ domains. In endothelial cells, plexin-B1 is coupled to Rho-and Aktdependent signaling pathways, 36,40 and there is some evidence that this is the case in platelets as well.…”
Section: Receptor-ligand Interactions At the Junctions Between Plateletsmentioning
confidence: 99%
“…36,37 CD72 is a 45-kDa immunoreceptor tyrosine-based inhibitory motif (ITIM) domaincontaining type II transmembrane protein that has been shown to affect intracellular signaling in B cells through its ability to associate with the tyrosine phosphatase SHP-1 and the adaptor protein Grb2. 38,39 Plexin-B1 has a type-I PDZ ligand domain at its C terminus, enabling it to interact with cytosolic proteins that have 1 or more PDZ domains. In endothelial cells, plexin-B1 is coupled to Rho-and Aktdependent signaling pathways, 36,40 and there is some evidence that this is the case in platelets as well.…”
Section: Receptor-ligand Interactions At the Junctions Between Plateletsmentioning
confidence: 99%
“…Single-cell suspensions from adult spleens were stained with different mixtures of fluorochrome-conjugated Abs (prepared at Stanford or obtained from BD Pharmingen) containing IgM (DS-1), IgD (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26), B220 (RA3-6B2), CD5 (53-7.3), CD21 (7G6), CD23 (B3B4), CD16/32 (2.4G2), CD72 (K10.6), CD22 (Cy34.1), and CD19 (1D3). These stain sets also contained Cascade Blue-conjugated CD3⑀ (145-2C11), CD4 (GK1.5), CD8␣ (53-6.7), Gr-1 (RB6-8C5), and F4/80 Abs that are used to gate out irrelevant, non-B cells.…”
Section: High-dimension Facs Analysismentioning
confidence: 99%
“…In contrast, Ogimoto et al (17) recently reported that CD72-deficient BAL-17 cells, a murine mature B lymphoma line, had impaired activation of ERK and JNK, but not p38, after anti-IgM stimulation, even though the CD72-deficient cells exhibited enhanced DNA synthesis. Similarly, Baba et al (12) recently indicated that an immature B cell line lacking CD72, although hyperproliferative to BCR stimulation, had less NF-B activity, less ERK activation, and no difference in p38 activation after BCR cross-linking with anti-IgM compared with its wild-type (WT) counterpart. These discrepancies may result from the different reagents (Ag vs anti-IgM) used to stimulate the BCR (10) or from the use of B cell lines at different developmental stages (immature vs mature) (18 -20).…”
mentioning
confidence: 92%
See 2 more Smart Citations